2019
DOI: 10.1302/0301-620x.101b7.bjj-2018-0943.r4
|View full text |Cite
|
Sign up to set email alerts
|

High re-operation and complication rates 11 years after arthrodesis of the wrist for non-inflammatory arthritis

Abstract: Aims Plate and screw fixation has been the standard treatment for painful conditions of the wrist in non-rheumatoid patients in recent decades. We investigated the complications, re-operations, and final outcome in a consecutive series of patients who underwent wrist arthrodesis for non-inflammatory arthritis. Patients and Methods A total of 76 patients, including 53 men and 23 women, with a mean age of 50 years (21 to 79) underwent wrist arthrodesis. Complications and re-operations were recorded. At a mean fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…They state that arthrodesis of the third CMC joint should be performed in patients with good soft tissue and normal-sized hands. 16 On the contrary, Nagy et al reported that 20 (43%) patients developed nonunion among 47 patients who underwent arthrodesis of the third CMC joint with plate removal. Eleven (23%) of these were painful and required Tenosynovitis, n (%) 10 (4.7)…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…They state that arthrodesis of the third CMC joint should be performed in patients with good soft tissue and normal-sized hands. 16 On the contrary, Nagy et al reported that 20 (43%) patients developed nonunion among 47 patients who underwent arthrodesis of the third CMC joint with plate removal. Eleven (23%) of these were painful and required Tenosynovitis, n (%) 10 (4.7)…”
Section: Discussionmentioning
confidence: 96%
“…They reported that the most frequent complication was pain over the plate/breakage (42%) followed by nonunion (4%). 16 Rauhaniemi et al included 115 patients with rheumatoid arthritis who underwent a TWF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations